A Multipath Transmission System for Information-Centric Networking Based on Standalone Name Resolution - Lin Jiang; Haojiang Deng; Shoujiang Dang (Applied Sciences, 2023)
Information-Centric Networking (ICN) essentially supports multipath transmission. However, current multipath schemes in ICN either necessitate major network infrastructure updates or necessitate specific network settings for terminal devices. To solve these problems, we propose MPTS-ICN, a multipath transmission system for ICN that realizes end-to-end multipath transmission. Taking the ICN architecture based on the standalone name resolution approach as a basis, MPTS-ICN is easier to implement and deploy than other ICN multipath schemes. Moreover, we have extended the original network layer protocol to support multipath data transmission in ICN. To set up concurrent transmission multipath efficiently, we propose a heuristic algorithm for the selection of multipath service nodes. Extensive experimental comparisons with existing data transmission methods show that in bandwidth-constrained scenarios, MPTS-ICN outperforms the best-route method by 83.6% and the ECMP method by 79.7% in average flow completion time.